The Usability Of Bridge-A Course Book Of Intermediate Practical Chinese At Chinese Department Binus University - Fu Ruomei (Bina Nusantara University, 2012)
This article discusses about the usability of Bridge-A Course Book of Intermediate Practical Chinese at Chinese Department BINUS University. Based on research, lecturers and students agree that this book has fulfilled the requirements as classroom textbook for Intermediate level including grammar, vocabulary and reading text. However, some materials cannot be easily understood due to cultural differences. Therefore, in order to get the most out of the book, teachers are expected to explain vocabularies in its specific context and background, and select appropriate reading text that relates to Indonesian values such as religion and culture.